(untitled) (Maritime Park: Journal of Maritime Technology and Society, 2026)
This study aims to analyze the factors that cause the difference in mooring service time between the Statement of Fact (SoF) issued by ITL Shipping Agency and the Pranota issued by PT Pelindo Balikpapan Branch. The research method employed was a qualitative method with a case study approach, with analysis conducted using fishbone diagrams to identify the gaps that emerged. The results of the study show that the main causes of time differences are seen from six aspects: Man, Machine, Method, Measurement, Material, and Mother Nature. This condition results in differences in the recording of mooring times, which have a direct effect on the calculation of mooring service costs and differences in bill values. This study emphasizes that improvement efforts need to be focused on improving the competence of Human Resources (HR), synchronizing the time recording system, strengthening the socialization of SOPs, optimizing document verification, and standardizing the time reference using UTC+08:00. These strategic steps are considered important to minimize time mismatches in the future and ensure the smooth and accurate process of mooring services at the Port of Balikpapan.